(untitled) (Journal of actual problems of jurisprudence, 2023)
Political instability, economic sanctions and a decline in the world community’s confidence in the state financial system have led to the evolution and creation of a new financial system that is not yet regulated by law. The article analyzes the current financial system and the legislation of the Republic of Kazakhstan in the field of production and circulation of digital assets. The above statistics on the growth of commercial fraud and an overview of existing digital assets on the market, their trading options showed the insufficiency of their legal regulation. The problems of countering unscrupulous projects are highlighted on the example of investment projects using digital assets in the «Finiko» and «C projects.Invest». As a result of the review, conclusions were drawn about the need to create a specialized authorized body in the field of digital assets with the involvement of qualified experts and discussion of systemic problems in the scientific community, it is also proposed to create a Committee for Innovative Financial Services, make amendments and additions to legislative acts to create an authorized body and further develop the infrastructure of the digital asset industry. Take measures to ensure quality education to increase the level of legal literacy of the population as a whole. Keywords: currency, commercial fraud, cryptocurrency, pump and dump, rag pool, token, transnational organized crime, financial pyramids, digital assets.